Formation of eating habits in early childhood: benefits of healthy eating (Research, Society and Development, 2021)
Introduction: Eating habits in early childhood must be observed from beginning to end, as the nutritional monitoring of the child will promote the best development of their organism and body in this primordial phase. General Objective: elucidate eating habits in early childhood. Methodology: To carry out this study, we opted for a research in the form of a deductive bibliographic review. Results and Discussion: From a nutritional point of view, Exclusive Breastfeeding (EBF) is the most nutritious and adequate food for a child up to the first six months of life, as it is rich in vitamins, proteins, carbohydrates, fats, minerals and water. Conclusion: In addition to understanding the role of the nutritionist in the child's development, the importance of parental involvement at this stage should be noted, given the value of nutrition education being addressed from an early age and taken by the little ones for the rest of their lives, influencing the formation of eating habits in adult life and taking it from generation to generation.